"ANALYSIS OF THE WORK ENVIRONMENT AND WORK MOTIVATION OF EDUCATION, YOUTH AND SPORTS OFFICES IN BANDUNG CITY” - Rohendra, Titto; Kamil, Insan; Ariefaldy, Jody; Isbandi, Arista; Sinatria, Raden Edra Faza; Syudur, Dede Adlan Akhmadus (CENTRAL ASIA AND THE CAUCASUS, 2022)
Human resources have a major role in every company activity. Human resources are still the main focus and foundation for companies to survive in the era of globalization. Some HR management activities such as procurement, assessment, protection, motivating employees, empowering employees, improving discipline, guidance, etc. One of the ways to improve employee performance is to pay attention to environmental factors and work motivation. The organization as the parent company must provide a comfortable and conducive work environment that is able to provoke employees to work productively. This means that every employee must be motivated at work. Facing the current era of globalization which demands high employee productivity, there are still many obstacles in the field so that it can hinder the vision of DISPORA Bandung City. Work Environment and Work Motivationjointly affect employee performance by 1.9% + 34.2% = 36% (R2 = 0.3603). The magnitude of the proportional influence caused by other variables outside of the work environment and work motivation variables, is expressed by 2Y , that is equal to (0.799791223)2 = 0.639666 or equal to 63.97%.